2000
DOI: 10.1081/clt-100102010
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazine, Butyrophenone, and Other Psychotropic Medication Poisonings in Children and Adolescents

Abstract: The presentation of phenothiazine and butyrophenone ingestions in children and adolescents may be nonspecific and confounded by coingestants. Patients with dystonias had more extensive neurologic testing than patients without dystonias, suggesting that physicians may not recognize dystonias as a clinical finding characteristic of phenothiazine or butyrophenone exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…These studies were from Italy, [4][5][6] the United Kingdom, 7 and the United States. 8 The US study was found to be a case series concerned with phenothiazine and butyrophenone poisonings. A large number of additional pharmacoepidemiologic studies from the United States and other countries were identified through the scanning of reference lists, including 2 reviews identified in the search.…”
Section: Methodsmentioning
confidence: 99%
“…These studies were from Italy, [4][5][6] the United Kingdom, 7 and the United States. 8 The US study was found to be a case series concerned with phenothiazine and butyrophenone poisonings. A large number of additional pharmacoepidemiologic studies from the United States and other countries were identified through the scanning of reference lists, including 2 reviews identified in the search.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] In developing countries, poisoning has also been recognised as a major health problem among children and adolescents. [11][12][13] Ahmed and Andersson compared the mortality rates of unintentional injuries, including poisoning, in countries with different income levels, and found that poisoning is the second most common cause of death in all lower and upper middle income countries among the [15][16][17][18][19][20][21][22][23][24] year age group. 12 Certain poison types of medicinal and non-medicinal substances have been identified as common agents in poisoning in children and adolescents.…”
mentioning
confidence: 99%
“…12 Certain poison types of medicinal and non-medicinal substances have been identified as common agents in poisoning in children and adolescents. [14][15][16][17] Riordan et al reviewed the literature on childhood poisoning and identified several groups of medicinal substances as the most common. 14 15 These included analgesics, anti-inflammatory agents, psychotropic drugs such as antidepressants, and benzodiazepines related agents.…”
mentioning
confidence: 99%
“…Although the great majority of reported cases of pediatric toxicity from phenothiazines result from chlorpromazine, James et al reported a 19-month-old who developed altered mental status (Glasgow Coma Scale score of 9) and a prolonged QTc after ingesting 38 mg/kg of thioridazine (48). The highest dose thioridazine tablet available is 200 mg, thus, a 10-kg child could ingest this amount with just two pills.…”
Section: Literature Reviewmentioning
confidence: 98%